Application of Hub-and-spoke Networks in Sparse Markets The Case of Africa. (1st May 2013) - Ssamula, Bridget; Venter, Christoffel
Hub-and-spoke networks hold promise for decreasing costs and increasing connectivity in air transport markets in countries characterised by sparse demand conditions. This paper examines suitable hub-location and network design methodologies, and the potential evolution of sparse networks over time in Africa. By adopting a cost model to assess the operational effectiveness of alternative networks, we show that low-cost, short-range airplanes have a significant role to play in low-density hub-and-spoke operations. In Africa, a four-hub network centred on high-demand hubs with short node-hub distances is the most suitable option.